Decentralization and Local Government Structures: Key to Strengthening Democracy in Pakistan - Adam Saud; Kashif Ali Khan (Journal of Political Studies, 2016)
Ever since the creation of the country in 1947, Pakistan has tried to form its constitutional foundations on a federalist system of government. Over the years, there have been several attempts at devolving power and resources to the provinces and consequently decentralizing that political and fiscal administration to the lowest levels. However, the lack of continuity in implementing these reforms and power struggle between central and provincial governments has resulted in an inconsistent history of decentralization in Pakistan. Democracies especially have laid less focus on decentralization especially when it has come to the creation of local governments and decentralized administrative structures. With representatives in the national and provincial legislatures often being inaccessible to their constituencies, local governments and representatives from the communities appear as a viable means to efficient service delivery